När tystnad binder - En analys av passivitetsverkningar i svensk avtalsrätt - Mellqvist,Viola (2025)
The starting point in Swedish contract law is that legal effects require active actions. Contracts are normally considered to arise through an exchange of mutual declarations of intent in the form of an offer and acceptance. Passivity, i.e. failure to act, does not, as a general rule, lead to contractual obligations. This arrangement is based on freedom of contract and the principle of intent, according to which a party is only bound by what it has intended to be bound by. The purpose of this thesis is to investigate under what conditions passivity, despite the general rule, can be given legal significance in Swedish law and what legal consequences may follow from a party's passivity. The Contracts Act does not contain a general rule on passivity, but it does contain certain provisions where failure to act can lead to contractual obligations. These rules are based on considerations of loyalty and aim to prevent one party from taking advantage of the other party's misconception or speculating at their expense. In these situations, passivity can serve as a substitute for a declaration of intent. Outside the area regulated by law, general principles of passivity have been developed in practice and doctrine. Passivity can be attributed legal effect either as a legal act, when, together with other circumstances, it can be interpreted as a declaration of intent according to the principle of reliance, or as an independent legal fact, when a legal norm attaches specific legal effects to failure to act. With regard to passivity as an independent legal fact, there are both written and unwritten norms. The decisive factor is whether the other party had justified confidence that the passive party had accepted a certain legal situation, or whether the passivity appears to be disloyal. The main legal effects of passivity in contract law are contractual binding and loss of rights. Contractual binding through passivity arises primarily with regard to the reliance principle, while loss of rights may occur through failure to give notice, limitation periods, or unwritten principles whereby a party is deemed to have waived its rights or allowed the other party to arrange its affairs on the basis of a certain legal situation. Case law shows that the principle of loyalty plays a central role in assessing the legal effects of passivity. Contracting parties are expected to keep each other informed and to clarify their positions where silence would otherwise risk misleading the other party. In summary, passivity constitutes an exception to the main rule of contractual binding through active declarations of intent, but has developed into a significant instrument for maintaining loyalty and efficiency in contractual relationships.
Keywords: Avtalsrätt; Passivitetsverkan